Expresión corporal (2003)
El trabajo de grado expone la relación del cuerpo físico con el entorno. Elcuerpopropioposeeunaespacialidad,ocupaunlugarfísicoenrelaciónconlasdemáscosas,yestandoenacciónpartedeestapremisa.Tambiénsomosparalosdemásunapersonaconuncuerpoconcretoenrelaciónalcualhayunaproximidad,unencuentrooindiferenciaposibles.Laexpresióncorporalsonlossentimientosypercepcionesquesetienenysetrasmitenpormediodelosmovimientosdelcuerpo;aunquesonúnicosypersonalesnosepuedenegarquehayansidoaprendidosenlaculturadondesenació